Comparison of the DES Cryptographic Algorithm and the AES Algorithm in Securing Document Files - Suwarni, Meli; Wahyudi, Jusuf; Khairil, Khairil (Jurnal Media Computer Science, 2023)
The document file security application at the Bengkulu City Education Office was made using the Visual Basic .Net programming language. In this application, 2 cryptographic algorithms have been implemented that can be used to secure document files, especially the employee payroll list file, namely the DES algorithm and the AES algorithm. In addition, this application has also embedded a process to analyze the comparison of the DES and AES algorithms, so that it can be known which algorithm is better to use. The comparison aspect consists of 2 aspects, namely processing time and file size after processing. Based on the tests that have been carried out, it can be concluded that the document file security application at the Bengkulu City Education Office is capable of carrying out the process of encrypting and decrypting document files and the functionality of the application has run as expected. From the test data that has been carried out by the encryption and decryption process, the results obtained based on the encryption processing time show that the AES algorithm is faster than the DES algorithm, based on the decryption processing time it is found that the AES algorithm is faster than the DES algorithm, based on the file size after the encryption process it is found that the DES algorithm and the AES algorithm have the same file size, based on the file size after the decryption process it is found that the DES algorithm and the AES algorithm have the same file size